The A/T1381 polymorphism in the A1-domain of von Willebrand factor influences the affinity of von Willebrand factor for platelet glycoprotein Ibα - Szántó, Tímea; Schlammadinger, Ágota; Staelens, Stephanie; De Meyer, Simon F.; Freson, Kathleen; Pareyn, Inge; Vauterin, Stephan; Hársfalvi, Jolán; Deckmyn, Hans; Vanhoorelbeke, Karen (Thrombosis and Haemostasis, 2007)
Many polymorphisms in vonWillebrand factor (VWF) have been reported and their association with VWF plasma levels or cardiovascular diseases has been investigated. The aim of this study was to examine whether the amino acid polymorphis mA/T1381 in the VWF A1-domain would affect VWF binding to platelet GPIbα. Sixty-one normal individuals were genotyped at the A/T1381 locus. Twenty-one A/A1381 homozygotes, 30 A/T1381 heterozygotes and 10 T/T1381 homozygotes were identified. Remarkably, when compared to VWF of A/T1381 and A/A1381 individuals, VWF of individuals carrying the T/T1381 variant showed an increased affinity for its platelet receptor GPIbα under static conditions, as reflected by an increased sensitivity to low concentrations of ristocetin or botrocetin. In addition, also the rVWF-T1381 demonstrated a higher affinity for GPIbα than rVWF-A1381. Interestingly, this enhanced affinity of the T/T variant over the A/T and A/A variant was, however, too subtle to affect platelet adhesion under physiological flow conditions, which fully corroborates the normal haemostatic phenotype of all individuals. We demonstrate that the VWF A/T1381 polymorphism plays an important role in inter-individual variability of the affinity of VWF for GPIbα, with T/T variants having a higher affinity than A/A and A/T variants, at least under static conditions in vitro. Further genetic linkage and association studies are necessary to establish whether the A/T1381 polymorphism could correlate with an increased risk of thrombotic events.
Keywords: von Willebrand factor; platelet glycoprotein Ibα; A/T1381 polymorphism; vonWillebrand disease; thrombosis